2006
DOI: 10.1007/s10880-006-9043-6
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregivers of Women with Physical Disabilities

Abstract: Cross-sectional, correlational analyses of data from two separate studies were conducted to examine the correlates of adjustment among family caregivers of women with disabilities. Participants included 40 caregivers of women with spinal cord injuries in the first study and 53 caregivers of women with cerebral palsy, traumatic brain injury, and other neuromuscular disabilities in the second study. It was hypothesized that a negative problem-solving style would be associated with greater caregiver distress in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
2
11
0
1
Order By: Relevance
“…The use of health and behavior codes (which were designed to be a solution to this recognized problem in pediatric psychology) has a solid foundation in a comprehensive biopsychosocial model of medical illness, yet has not found its way into practice on multiple levels, including: (a) practitioner awareness and use, (b) institutional support, (c) state policy, or (d) private insurance recognition. The themes presented here echo challenges noted previously 15 indicating that the use of health and behavior codes is still impacted by many barriers, including the rejection of claims on the basis of elements that are written into the code procedures (e.g., use of medical diagnosis code and medical insurance dollars for behavioral health intervention).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The use of health and behavior codes (which were designed to be a solution to this recognized problem in pediatric psychology) has a solid foundation in a comprehensive biopsychosocial model of medical illness, yet has not found its way into practice on multiple levels, including: (a) practitioner awareness and use, (b) institutional support, (c) state policy, or (d) private insurance recognition. The themes presented here echo challenges noted previously 15 indicating that the use of health and behavior codes is still impacted by many barriers, including the rejection of claims on the basis of elements that are written into the code procedures (e.g., use of medical diagnosis code and medical insurance dollars for behavioral health intervention).…”
Section: Discussionsupporting
confidence: 62%
“…Evaluations within institutions have generally found that while health and behavior codes provide higher reimbursement than mental health codes, coverage is more often denied with health and behavior codes as compared to mental health codes. 15, 16 Within a pediatric obesity program, collections using health and behavior codes were particularly problematic for group treatment and family intervention without the patient present. 17 These types of analyses are limited in that they provide institution specific data that depends on state Medicaid and private insurance recognition of the codes.…”
mentioning
confidence: 99%
“…In Sweden, a person with pronounced disability can get 'personal assistance' subsidized by the government (Barron, Michailakis, and Sö der 2000). According to a US study mothers were more likely than other members of a family to become a caregiver (Rivera et al 2006). A Swedish qualitative study (Whitaker 2008) showed that parents are caregivers even if their disabled children are adults and have personal assistants.…”
Section: Introductionmentioning
confidence: 99%
“…One of the first studies of family caregivers of women with disabilities found that mothers were more likely to assume the caregiver role than other family members (Rivera et al, 2006). Furthermore, this study found that caregiver problem-solving abilities accounted for more variance in caregiver depression and well-being than their demographic characteristics and disability severity of the care recipients.…”
Section: Introductionmentioning
confidence: 99%